2002
DOI: 10.1093/bja/88.6.809
|View full text |Cite
|
Sign up to set email alerts
|

Epidural analgesia with 0.15% ropivacaine plus sufentanil 0.5 µg ml–1 0.10% bupivacaine plus sufentanil 0.5 µg ml–1: a double‐blind comparison during labour

Abstract: Combined with sufentanil 0.5 microgram ml-1, 0.10% bupivacaine and 0.15% ropivacaine produce effective and equivalent analgesia during labour, with similar incidences of motor block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Ten studies 11,12,[15][16][17][18][19][20][21][22] were finally selected by following inclusion and exclusion criteria. The study screening and selection process is depicted in Figure 1 and the characteristics of the included studies including patients' demographic and obstetric data, and concentration of anesthetics used in each study is presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies 11,12,[15][16][17][18][19][20][21][22] were finally selected by following inclusion and exclusion criteria. The study screening and selection process is depicted in Figure 1 and the characteristics of the included studies including patients' demographic and obstetric data, and concentration of anesthetics used in each study is presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas Buyse et al 15 have shown that the dose sparing effect of sufentanil is greater for bupivacaine (up to 90%) than for ropivacaine or levobupivacaine (up to 78%), van de Velde et al 11 in a dose-response study noticed that in combination with sufentanil, racemic bupivacaine is more potent than ropivacaine (1.4 times) and levobupivacaine (1.5 times) with ED95 of ropivacaine and levobupivacaine of 4.8 mg (95% CI, 4.0-6.7) and 5.0 mg (95% CI, 4.1-7.0), respectively. Wang et al 12 have calculated the EC50 and EC95 by using probit regression as: 0.044% (0.031%-0.056%) and 0.177% (0.138%-0.261%) for bupivacaine, 0.053% (0.039%-0.066%) (a) Clement et al 17 Fischer et al 18 Gautier et al 19 Gogarten et al 20 Hoffman-kiefer et al 21 Van de Velde et al 11 17 Fischer et al 18 Gautier et al 19 Gogarten et al 20 Hoffman-kiefer et al 21 Van de Velde et al 11 and 0.214% (0.165%-0.328%) for ropivacaine, and 0.052% (0.038%-0.064%) and 0.210% (0.164%-0.320%) for levobupivacaine, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, during the second stage of labor also VAS score was comparable at any time. Meister et al [14] and Clément et al [11] observed that VAS score was comparable in both the groups throughout the labor. In this study, Apgar score was between 7 and 10 in most of the neonates, 93.33% in Group B and in 100% in Group R at 1 min and at 5 min and 6.67% neonates in Group B and no neonate in Group R had Apgar score between 5 and 6 at 1 min and at 5 min.…”
Section: International Journal Of Medical Science and Public Healthmentioning
confidence: 91%
“…30 Numerous PCEA and epidural infusion studies found the volume requirements of ropivacaine and bupivacaine to be similar when used either in equal concentrations, or in Ôpotency-adjusted' designs. 42 The former are used to refute the MLAC findings, the latter to support! Indeed when PCEA has been used to compare different concentrations or doses of the same drug, such as ropivacaine 0.1% and 0.15% 43 again the volumes consumed have been similar despite a 50% difference in dose exposure.…”
Section: Potenciesmentioning
confidence: 99%